Hybrid Regimes of the Western Balkans: Reflection of a Global Geopolitical Struggle - Andjelic, Neven (Journal of Regional Security, 2020)
The new global order has yet to be fully established. The process reflects not only a geopolitical struggle but also a set of competitive political models. While it is possible to determine more than two dominant models, it is a contest between the two forms of democracy – liberal and illiberal. A one-party state, or a Chinese model, is an economic model used for geopolitical purposes while Muslim political model, strongly contested within the Muslim world, is restricted to areas dominated by the population of this faith. Some of its forms are reflected in the form of authoritarianism as developed in Turkey. The faith, therefore, is of lesser significance. The regimes in the Western Balkans have been developed and are based on two models of democracy. The resulting hybrid regimes are analysed in the global context of the power-struggle and ideological contest. The question is whether the hybrid regimes of the Western Balkans are the result of dysfunctional local democracy or whether the search for global stability is resulting in a model of competitive authoritarianism which provides for global security but also supports the regime’s desire to remain unchanged in perpetuity? This development might be supportive of international security but is an utterly destabilising factor for societies in the Western Balkans and a substantial obstacle to the development of liberal democracy.